Neural efficiency and proficiency adaptation of effective connectivity corresponding to early and advanced skill levels in athletes of racket sports. Issue 2 (2nd September 2022) - Gao, Qing; Luo, Ning; Sun, Mengli; Zhou, Weiqi; Li, Yan; Liang, Minfeng; Yang, Chengbo; Zhang, Mu; Li, Rong; Gong, Lisha; Yu, Jiali; Leng, Jinsong; et al.
Abstract: This study explored how the neural efficiency and proficiency worked in athletes with different skill levels from the perspective of effective connectivity brain network in resting state. The deconvolved conditioned Granger causality (GC) analysis was applied to functional magnetic resonance imaging (fMRI) data of 35 elite athletes (EAs) and 42 student‐athletes (SAs) of racket sports as well as 39 normal controls (NCs), to obtain the voxel‐wised hemodynamic response function (HRF) parameters representing the functional segregation and effective connectivity representing the functional integration. The results showed decreased time‐to‐peak of HRF in the visual attention brain regions in the two athlete groups compared with NC and decreased response height in the advanced motor control brain regions in EA comparing to the nonelite groups, suggesting the neural efficiency represented by the regional HRF was different in early and advanced skill levels. GC analysis demonstrated that the GC values within the middle occipital gyrus had a linear trend from negative to positive, suggesting a stepwise "neural proficiency" of the effective connectivity from NC to SA then to EA. The GC values of the inter‐lobe circuits in EA had the trend to regress to NC levels, in agreement with the neural efficiency of these circuits in EA. Further feature selection approach suggested the important role of the cerebral‐brainstem GC circuit for discriminating EA. Our findings gave new insight into the complementary neural mechanisms in brain functional segregation and integration, which was associated with early and advanced skill levels in athletes of racket sports. Abstract : The neural efficiency represented by regional hemodynamic response function (HRF) was different in early and advanced stages of motor training. The Granger causality (GC) values within the middle occipital gyrus (MOG) had a linear trend from negative to positive, suggesting a stepwise "neural proficiency" of the effective connectivity from normal controls (NC) to student‐athletes (SA) then to elite athletes (EA). While the GC values of the fronto‐parietal and fronto‐occipital circuits in EA had the trend to regress to NC levels, in agreement with the neural efficiency of these circuits in EA. Complementary neural mechanisms in brain functional segregation and integration were associated with different levels of sports experience in fast‐ball athletes.